2021
DOI: 10.1021/acs.joc.1c00835
|View full text |Cite
|
Sign up to set email alerts
|

Copper(II)-Catalyzed Tandem Reaction: Synthesis of Furo[3,2-c]coumarin Derivatives and Evaluation for Photophysical Properties

Abstract: An efficient protocol for synthesizing furo[3,2c]coumarin derivatives is described. The novel reaction could afford the desired furocoumarins with good to excellent yields in a mild and rapid manner. Large substrate scope screening and scaleup preparation have also been accomplished, and selected compounds were evaluated for their photophysical properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…The selected compounds exhibited strongly fluorescent properties with a high molar extinction coefficient (5750–9750 in methanol) and large Stokes shifts (7130–8020 cm –1 in methanol). Interestingly, with increasing solvent polarity, bathochromic shifts in fluorescence of the selected compounds were observed (for detail, see the Supporting Information), which may indicate that the fluorescence involves the formation of the intramolecular charge-transfer excited state …”
Section: Resultsmentioning
confidence: 97%
“…The selected compounds exhibited strongly fluorescent properties with a high molar extinction coefficient (5750–9750 in methanol) and large Stokes shifts (7130–8020 cm –1 in methanol). Interestingly, with increasing solvent polarity, bathochromic shifts in fluorescence of the selected compounds were observed (for detail, see the Supporting Information), which may indicate that the fluorescence involves the formation of the intramolecular charge-transfer excited state …”
Section: Resultsmentioning
confidence: 97%
“…The retrosynthetic analysis of the titled targeted conjugates revealed that their synthesis could be achieved by Cu(I)‐catalyzed Huisgen (3+2) cycloaddition reaction between 4‐azidocoumarins and 3′‐ O ‐propynyl‐2′‐dideoxyuridin or 3′‐ O ‐propynylthymidin (Scheme 1). Six 4‐azidocoumarin precursors 2 a – f were synthesized from their corresponding 4‐hydroxylcoumarins 1 a – f [24,25,26] by following literature procedure [27] …”
Section: Resultsmentioning
confidence: 99%
“…The reaction was monitored by thin-layer chromatography (ethyl acetate/petroleum ether = 1/1, v/v). After the reaction was completed, the reaction was cooled to room temperature, then extracted with dichloromethane (2 × 50 mL), and the organic layer was collected and washed with saturated saline (3 × 100 mL); the combined organic layers were dried with anhydrous sodium sulfate, filtered, and the filtrate was concentrated by a rotary evaporator to obtain the yellow crude product B , which could be used for the next step directly …”
Section: Methodsmentioning
confidence: 99%